Literasi Digital ASN Kabupaten Sumedang - Ika Wulandari; Ramdani Priatna; Fikri A.T Andikaputra (Jurnal PubBis, 2022)
The rapid development of technology should be balanced with the quality of human resources. It turns out that there are still many problems that occur related to information and communication technology. Not only from the general public, but also from the State Civil Apparatus. This study uses a qualitative method. Data were taken through questionnaires, interviews and secondary library sources. Based on the questionnaire distributed in Sumedang Regency, there are still many inaccurate answers related to digital literacy. In fact, this ability is very important at this time to carry out various government functions. One way that can be done as a solution is through training or training.